How will the reduction of tariffs and taxes on insecticide- treated bednets affect household purchases? - Jonathon L. Simon; Bruce A. Larson; Alexander Zusman; Sydney Rosen
One of the steps called for in the fight against malaria is the removal of tariffs and taxes on insecticide-treated bednets (ITNs), netting materials, and insecticides, with a view to reducing the retail prices of ITNs and thus increasing utilization. In this paper we develop an approach for analysing the extent to which reform of tariff and tax policy can be expected to increase ITN purchases. We consider the following questions: (1) How much does the retail price of ITNs change if tariffs and taxes are reduced or eliminated? (2) How responsive is consumer demand to changes in the retail price of ITNs? Data on the price elasticity of demand for ITNs are very limited. Nevertheless, they suggest that ITN demand is not highly responsive to lower prices if household preferences are held constant. The reduction in retail prices associated with the removal of tariffs and taxes depends on the structure of the market in individual countries. In Nigeria, reducing the tariff on insecticides from 42% to zero and the tariff on netting materials from 40% to 5% is expected to increase ITN purchases by 9-27%, depending on the elasticity used. Country-specific information about market structure and cost conditions is needed if predictions are to be made as to how a specific policy change will affect ITN purchases.